Vaccines against enteric infections for the developing world - Czerkinsky, Cecil (Philos Trans R Soc Lond B Biol Sci, 2015)
—. limited knowledge regarding the properties of the gut immune system during early life; —. lack of mucosal adjuvants, limiting mucosal vaccine development to live-attenuated or killed whole virus and bacterial vaccines; —. lack of correlates/surrogates of mucosal immune protection; and —. limited knowledge of the factors contributing to oral vaccine underperformance in children from developing countries. There are now reasons to believe that the development of safe and effective mucosal adjuvants and of programmatically sound intervention strategies could enhance the efficacy of current and next-generation enteric vaccines, especially in lesser developed countries which are often co-endemic for enteric infections and malnutrition. These vaccines must be safe and affordable for the world's poorest, confer long-term protection and herd immunity, and must be able to contain epidemics.